Allowable Pillar Width for Salt Cavern Gas Storage Based on Triangular Well Layout: A Case Study in China - Rui Cai; Hongling Ma; Xiaopeng Liang; Kai Zhao; Chunhe Yang (Energies, 2024)
Salt rock, renowned for its remarkable energy storage capabilities, exists in deep underground environments characterized by high temperature and pressure. It possesses advantageous properties such as high deformability, low permeability, and self-healing from damage. When establishing a cluster of salt cavern gas storage facilities, the careful selection of ore column widths between these reservoirs is crucial for minimizing the risk of structural failure, optimizing salt rock resource utilization, and enhancing the construction and operation of gas storage reservoirs. In current practices, square triangular arrangements are commonly used in designing well layouts for reservoir groups to balance stability and economic considerations. This study, conducted in the context of the Jintan salt cavern gas storage project in Jiangsu Province, employed FLAC3D to create a finite element model for proposed gas storage configurations. A comprehensive analysis of the long-term operational safety of salt cavern gas storage with triangular well layouts was carried out. Various indices were examined, covering aspects such as cavern wall displacement, characteristics of the plastic zone, volume shrinkage, safety coefficients, seepage range, pore pressure fluctuations, and seepage volume. The study also considered the mechanical behavior of hexagonal columns within the surrounding rock during extended storage operations, leading to the optimization of allowable widths for these columns. The results indicate that, at operating pressures ranging from 6.5 to 17 MPa, the permissible column width should exceed 1.67 times the maximum cavern diameter to ensure compliance with criteria for long-term stability and containment within a square triangular layout. These findings provide valuable insights into determining the optimal allowable widths of salt cavern columns for positive triangular layouts.